The chronic uncertainty of American Indian property rights. Issue 3 (7th June 2021) - Alston, Eric; Crepelle, Adam; Law, Wilson; Murtazashvili, Ilia
Abstract: Property institutions should ideally provide economic actors with certainty that their local choices about investment will not be unsettled by shifting political economic equilibria. We argue that for this to occur, political autonomy, administrative and enforcement capacity, political constraints, and accessible legal institutions are each necessary. A comparison of the evolution of property rights for settlers and American Indians in the United States shows how political and legal forces shape the evolution of property institutions. American Indians, who had property institutions before Europeans arrived, could not defend their land from Europeans and later Americans due to lacking military capacity. Settlers' property rights were relatively secure because the government had sufficient autonomy and capacity to broadly define and enforce their rights, political institutions constrained the government from expropriating settlers' property, and legal institutions provided a forum for settlers to adjudicate and defend their rights in court. Native Americans, in contrast, had systematically inconsistent and often expropriative policy treatment by the government. Although tribes have technically been sovereign since the 1970s, tribal governments continue to lack sufficient political and legal autonomy and capacity to define and enforce property institutions in response to evolving local conditions.